Conjugational Types in Croatian - Zrinka Jelaska; Tomislava Bošnjak Botica (Rasprave Instituta za Hrvatski Jezik i Jezikoslovlje, 2019)
This paper analyses a new classification of verb conjugation types in Croatian, which is based on both their canonical form – the infinitive, which is the non-finite verbal form par excellence, and the basic form – the present, which is on the other end of the finiteness scale. The first chapter provides a brief overview of Croatian conjugational typology, starting from the grammar by B. Kašić (1604) until the most recent grammars by Silić and Pranjković (2005), as well as Jelaska (2015), ranging from one up to twenty-nine categories. The recent typologies within structuralist, generative and cognitive approaches are described in more detail, especially in Jelaska and Bošnjak Botica (2012), where prototype-based categorization is argued for as the most appropriate categorization. The second part of the paper analyses some properties of the present classification into three groups (a, i, e) and ten types within them: the shape, productivity, size, usage and the relations between them. The data consists of 24,400 Croatian verbs, which are categorized into groups, types and subtypes. The first group has only one type as member (verbs such as gledati), the second has three members (verbs such as moliti, vidjeti and trčati), the third has six (verbs like pisati, smijati se, putovati, davati, viknuti, ići).